Effect of Dehydration on the Rheological Measurement of Surimi Paste in Cone-Plate Rheometry: Heat and Mass Transfer Simulation - Hyeon Woo Park (Processes, 2020)
Moisture transfer characteristics of Alaska pollock (AP) surimi were investigated at various temperatures. The effective moisture diffusivity increased from 5.50 × 10−11 to 2.07 × 10−9 m2/s as the temperature increased from 30 °C to 90 °C. In order to investigate the mass and heat transfer characteristics of AP surimi, the simulation model was developed and evaluated by root-mean-square error (RMSE) (<2.95%). Rheological properties of AP surimi were investigated at different heating rates (1 °C/min, 5 °C/min, 10 °C/min, 20 °C/min and 30 °C/min). As heating rate increased to 20 °C/min and 30 °C/min, elastic modulus (G’) significantly diminished. The diminished G’ could be explained by impaired gel during temperature sweep supported by the predicted temperature distribution in the simulation model. Changes in moisture content of AP surimi during temperature sweep were also measured and predicted by the simulation model. The results showed the decreased amount of moisture content significantly increased as heating rate increased.